A survey of graduate employment prospects, 1973/74 to 1975/76 - Federal Republic of Nigeria (Lagos : National Manpower Board, Federal Ministry of Economic Development and Reconstruction, 1974)
This report is the results of the "Survey of Graduate Employment Prospects" covering the period 1973/74 to 1975/76.
At head of title: Federal Republic of Nigeria.
Chiefly tables.
rpm 29/03/2018
Loans
Keywords: Employment; College graduates; Nigeria